2015
DOI: 10.1021/es505232f
|View full text |Cite
|
Sign up to set email alerts
|

Ball Milling Synthesized MnOx as Highly Active Catalyst for Gaseous POPs Removal: Significance of Mechanochemically Induced Oxygen Vacancies

Abstract: A rapid (1.5 h) one-step ball milling (BM) method was developed not only to modify commercial MnO2 via top-down approaches (BM0), but also to bottom-up synthesize MnO(x) by cogrinding of KMnO4 and MnC4H6O4 (BM1) or KMnO4 and MnSO4 (BM2). Catalysts activity on gaseous POPs removal was tested using hexachlorobenzene (HCBz) as surrogate. Catalytic performance decreases in the order of BM2 ≈ BM1 (T90% = 180-200 °C) > BM0 (260 °C) > CMO ≈ cryptomelane MnO2 (>300 °C). Both adsorption and destruction contribute to HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(66 citation statements)
references
References 47 publications
2
64
0
Order By: Relevance
“…The distance between reactants was shortened by the friction and wear performance between powders, furthermore, atomic spontaneous diffusion rate was directly increased by mechanical force as well, then chemical reaction was induced between EDTA and LiCoO 2 (Wu et al, 2013;Yang et al, 2015). The chelate reaction mechanism of EDTA-LiCoO 2 milling is shown below: It has been reported that metal chelates are cyclic structure of metal atoms and organic ligand formed by donation of electrons from the ligand donor atoms, usually oxygen, nitrogen, or sulfur is the electron acceptor metal ion.…”
Section: Reaction Mechanism Of Licoo 2 With Edta During Ball Millingmentioning
confidence: 99%
“…The distance between reactants was shortened by the friction and wear performance between powders, furthermore, atomic spontaneous diffusion rate was directly increased by mechanical force as well, then chemical reaction was induced between EDTA and LiCoO 2 (Wu et al, 2013;Yang et al, 2015). The chelate reaction mechanism of EDTA-LiCoO 2 milling is shown below: It has been reported that metal chelates are cyclic structure of metal atoms and organic ligand formed by donation of electrons from the ligand donor atoms, usually oxygen, nitrogen, or sulfur is the electron acceptor metal ion.…”
Section: Reaction Mechanism Of Licoo 2 With Edta During Ball Millingmentioning
confidence: 99%
“…For CaCO 3 /OMS‐2, the ratio of Mn (VI) species slightly increased, and simultaneously the value of Mn (II + III)/Mn (IV) decreased to 1.02. In addition, the average oxidation state (AOS) of Mn species can be estimated based on the magnitude of Mn 3 s doublet splitting . From the results given in Figure (b), the AOS values for OMS‐2 and CaCO 3 /OMS‐2 were 3.74 and 3.78, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the wide survey XPS spectra shown in Figure S5, the presence of Ca and C species in CaCO 3 /OMS‐2 was clearly observed as well as the K, Mn and O species, in good agreement with the EDS analysis. For the spectrum of Mn 2p region of OMS‐2 given in Figure (a), three characteristic peaks for Mn (IV) at 643.6 eV, Mn (III) at 642.3 eV and Mn (II) at 641 eV were observed, with a Mn (II + III)/Mn (IV) ratio of 1.04. For CaCO 3 /OMS‐2, the ratio of Mn (VI) species slightly increased, and simultaneously the value of Mn (II + III)/Mn (IV) decreased to 1.02.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent applications of mechanochemistry involve organic and organometallic synthesis, synthesis of coordination polymers, metal–organic frameworks (MOFs), asymmetric catalytic processes, and racemic resolution, and it has gained greater relevance in crystal engineering as well as in the pharmaceutical field . In addition, the industrial application of mechanochemistry has been demonstrated through the use of industrial ball‐milling in the synthesis of catalysts and other products …”
Section: Methodsmentioning
confidence: 99%